2018
DOI: 10.1111/acel.12812
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 stabilization prevents critical oxidative damage in Down syndrome cells

Abstract: SummaryMounting evidence implicates chronic oxidative stress as a critical driver of the aging process. Down syndrome (DS) is characterized by a complex phenotype, including early senescence. DS cells display increased levels of reactive oxygen species (ROS) and mitochondrial structural and metabolic dysfunction, which are counterbalanced by sustained Nrf2‐mediated transcription of cellular antioxidant response elements (ARE). Here, we show that caspase 3/PKCδdependent activation of the Nrf2 pathway in DS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 57 publications
4
52
0
Order By: Relevance
“…Nrf‐2 induces transcription of various antioxidant enzymes such as glutathione S‐transferase, NAD(P)H:quinone oxidoreductase 1, catalase. Studies have been associated on the protective role of Nrf‐2 against oxidative damage in down syndrome, Amyloid beta formation . In this study we found that, DOX downregulated Nrf‐2 and its target gene expressions such as HO‐1 and NQO1 levels.…”
Section: Discussionmentioning
confidence: 50%
“…Nrf‐2 induces transcription of various antioxidant enzymes such as glutathione S‐transferase, NAD(P)H:quinone oxidoreductase 1, catalase. Studies have been associated on the protective role of Nrf‐2 against oxidative damage in down syndrome, Amyloid beta formation . In this study we found that, DOX downregulated Nrf‐2 and its target gene expressions such as HO‐1 and NQO1 levels.…”
Section: Discussionmentioning
confidence: 50%
“…Pathways upregulated pathways in Sin3a-LOF AT2 cells compared to wildtype AT2 cells included oxidative phosphorylation, mitochondrial dysfunction, sirtuin signaling, EIF2 signaling, and mTOR signaling, which were all identified in our bulk AT2 cell RNA-seq analyses. In addition, our scRNA-Seq data revealed differential expression of several other genes and pathways linked to cellular senescence, including eIF4 and p70S6K (46), protein ubiquitination (56,57), PI3K/AKT signaling (21)(22)(23)(24), phagosome maturation (58,59), VEGF signaling (60), integrin signaling (61), NRF2mediated oxidative stress (62)(63)(64)(65), actin nucleation (66), and MAPK signaling (67-69) ( Fig 2H).…”
Section: And Supplementalmentioning
confidence: 90%
“…Short-term SOD2 depletion in mouse embryos increases mtROS; however, at the postnatal stage, it activates antioxidant defense by Nrf2 and remodels mitochondrial function in the liver [13]. In fibroblasts derived from Down syndrome patients, elevated mtROS production is counteracted by Nrf2, which is activated by PKCδ-mediated phosphorylation [14]. The expression of mitochondrially targeted catalase (mtCAT) alleviates oxidative stress and inhibits Nrf2 activation in fibroblasts from Down syndrome patients [14].…”
Section: Introductionmentioning
confidence: 99%